Peri Mestike Mempertahan Bahasa dan Budaya Gayo - Joni (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The Gayo language is one of the regional languages rich in meaning and cultural values. The Gayo language has two varieties of modes: the ordinary spoken Gayo language used by the current generation and the Gayo customary language known as PM (Peri Mestike). The PM language contains profound meanings and features modes of speech, namely metaphorical and indirect, or can be referred to as indirect and non-literal speech. The preservation of the Gayo language through customary language, especially in the practice of peri mestike, is important for maintaining the cultural identity of the Gayo community. This study discusses how the customary language (PM) functions as a medium for preserving the Gayo language and the cultural values contained within it.